Antimicrobial stewardship: an evaluation of structure and process and their association with antimicrobial prescribing in NHS hospitals in England. (11th January 2019) - Scobie, Antonia; Budd, Emma L; Harris, Ross J; Hopkins, Susan; Shetty, Nandini
Abstract: Background: Rigorous antimicrobial stewardship programmes (ASPs) are an essential strategy against antimicrobial resistance. Objectives: To evaluate and score ASPs in acute English NHS hospitals and determine association of ASP scores with antimicrobial prescribing. Methods: ASP structure and process were evaluated through an online survey in 148/152 acute hospitals in 2017. Scores were assigned to quality indicators based on resource- and labour-intensiveness, and their association with total and modified WHO-categorized 'Access', 'Watch' and 'Reserve' (AwaRe) prescribing was analysed. Results: The survey response rate was 97% with 78% of trusts submitting antimicrobial prescribing data. Over 80% of ASPs contained stewardship teams, policies and access to outpatient parenteral antimicrobial therapy, whilst less than 50% scored well for leadership or funding. High process performance was observed for antimicrobial pre-authorization, prescribing review and feedback, restricted susceptibility reporting, antimicrobial consumption monitoring, adherence to guidelines and junior doctor training. Low process attainment included education of senior prescribers and lack of resistance surveillance data distribution. Between 2016 and 2017, there was no difference in total trust prescribing ( P = 0.117) although carbapenem prescribing fell (incidence rate ratio = 0.93, 95% CI 0.88–0.98) in non-teaching hospitals; 'Watch' prescribing also increased for specialist hospitals (OR = 1.10, 95% CI 1.01–1.20), as did 'Reserve' category prescribing in teaching (OR = 1.58, 95% CI 1.23–3.02) and specialist hospitals (OR = 3.09, 95% CI 2.02–4.74). A high process score was associated with lower 'Reserve' prescribing (OR = 0.82, 95% CI 0.67–1.01). Conclusions: All responding trusts had established ASPs. The association of a scoring system with total and 'AWaRe' prescribing to assess effectiveness of ASPs merits further study.